The psychodiagnostic opportunities in suicide risk assessment - Gailienė, D.; Knabikienė, G.; Asminavičiūtė, R. (Psichologija, 1990)
Different suicidality research has found that suicide, as a rule, is the result of quite a long process. Thus, in order to prevent suicides, it is important to distinguish the reliable indicators of increased suicide risk. It is attempted to use various biochemical, clinical and psychodiagnostic indicators for this matter.The possibility of using the purpose of life index as suicide risk indicator was tested. The purpose of life index was tested by using Crumbaugh and Maholic Purpose of life test. The results showed the relationship between the purpose of life index and intensity of suicidal tendencies. The indicator of suicide risk is the decrease in the purpose of life index simultaneously with positive or neutral attitude to suicide. Since Crumbaugh and Maholic test is a direct assessment tool, it should be used in along with other methods.
Keywords: purpose of life; purpose of life index; suicide risk; suicide